THE CRITICAL EVENT AND RECOGNITION OF NET PROFIT. - Myers, John H. (The Accounting Review, 1959)
Abstract The article reviews the economic concept of net income and the accounting procedure in a number of specific business situations, and then suggests a principle, which is compatible with economic theory and at the same time coordinates most current accounting practice. The matching of cost and revenue has grown during the past fifteen or twenty years into a cardinal principle of accounting. Economic theorists since the days of Adam Smith have spoken of land, labor, and capital as the three factors of production. Compensation to these factors has been known as rent, wages, and interest. Under a perfectly functioning system, these three factors receive all the income. Any residual that remains in an actual case is due to the imperfections of the system in the individual case at the particular moment of time. Later economists acknowledged a fourth factor of production: entrepreneurship. Its compensation is known as profit. Profit is the reward for bearing risk; the risk of enterprise, the risk of venturing in business, the risk of owning something in hope of selling it later.